2019 31st International Symposium on Power Semiconductor Devices and ICs (ISPSD) 2019
DOI: 10.1109/ispsd.2019.8757624
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of BTI in SiC MOSFETs Using Third Quadrant Characteristics

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…The initial peak shift is more noticeable for the higher gate voltage stress. This agrees with the literature, which reports an increased VTH shift with stress voltage level [2], [19], [20] A significant observation already reported in [34] is the existence of the phenomenon of dip-and-rebound at high gate voltage stresses (35 V) in the evaluated planar SiC MOSFET. This phenomenon was also observed for Si MOSFETs [36], at gate stress levels of 65 V.…”
Section: Crosstalk Evaluationsupporting
confidence: 92%
See 1 more Smart Citation
“…The initial peak shift is more noticeable for the higher gate voltage stress. This agrees with the literature, which reports an increased VTH shift with stress voltage level [2], [19], [20] A significant observation already reported in [34] is the existence of the phenomenon of dip-and-rebound at high gate voltage stresses (35 V) in the evaluated planar SiC MOSFET. This phenomenon was also observed for Si MOSFETs [36], at gate stress levels of 65 V.…”
Section: Crosstalk Evaluationsupporting
confidence: 92%
“…As introduced in [34], an interesting feature of the body diode method is that it allows the study of pulsed stresses. Tests have been performed using different devices at different gate voltage stresses.…”
Section: Crosstalk Evaluationmentioning
confidence: 99%
“…In [26][27][28], it was shown how the third quadrant characteristics of SiC MOSFETs can be used as an indicator of VTH for tracking the peak shift and recovery of VTH after gate stress. In the case of SiC MOSFET, the methodology is based in the relationship between VTH and VSD at low currents when VGS=0.…”
Section: Threshold Voltage Instability Characterization Methodologymentioning
confidence: 99%
“…This can reveal transient mechanisms hindered in the long stress sequences. In the case of SiC [28], it was able to reveal the phenomenon of dip-and-rebound of the threshold voltage at highly accelerated stress levels. This can be highly relevant for evaluating the results obtained for the Schottky Gate GaN The pulse sequence selected for these investigations consists of 2 s at the defined stress voltage VSTRESS and 2 s at 0 V for 40 cycles.…”
Section: A Repetitive Pulse Gate Stressesmentioning
confidence: 99%
“…Focusing on threshold voltage characterization, the value of VGD-TH and VGS-TH can be assumed equal [2] and at low currents the voltage drop in the resistance RSD can be considered negligible. Analyzing (1), it can be concluded that during reverse conduction of a small sensing current at VGS=0, VSD is an indicator of VTH (VSD≈VTH The direct relationship between VSD and VTH indicates that the method presented in [24,25] could be used for monitoring VTH shift in GaN HEMTs. This method is similar to the use of the body diode voltage as a TSEP in MOSFETs [14].…”
Section: Vsd=vgd-th -Vgs +I•rsd (1)mentioning
confidence: 99%